2008
DOI: 10.21273/hortsci.43.5.1479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saline Water Irrigation on Growth and Physiological Responses of Three Rose Rootstocks

Abstract: Salt-tolerant landscape plants are needed for arid and semiarid regions where the supply of quality water is limited and soil salinization often occurs. This study evaluated growth, chloride (Cl) and sodium (Na) uptake, relative chlorophyll content, and chlorophyll fluorescence of three rose rootstocks [Rosa ×fortuniana Lindl., R. multiflora Thunb., and R. odorata (Andr.) Sweet] irrigated with sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
5
16
1
Order By: Relevance
“…fruticosa, E. septentrionale, and T. acaulis irrigated with saline solution at an EC of 10.0 dS · m -1 decreased by 71.3%, 56.3%, 69.7%, and 48.1%, respectively. Elevated salinity has been reported to reduce plant shoot dry weight in various ornamental plants such as A. canadensis, aster perennials, E. laxum, and rose rootstocks (Hadi et al, 2014;Niu et al, 2008;Wu et al, 2016aWu et al, , 2016b. This is a consequence of salinity-induced water deficit, resulting in stunted growth and reduced leaf size described earlier.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…fruticosa, E. septentrionale, and T. acaulis irrigated with saline solution at an EC of 10.0 dS · m -1 decreased by 71.3%, 56.3%, 69.7%, and 48.1%, respectively. Elevated salinity has been reported to reduce plant shoot dry weight in various ornamental plants such as A. canadensis, aster perennials, E. laxum, and rose rootstocks (Hadi et al, 2014;Niu et al, 2008;Wu et al, 2016aWu et al, , 2016b. This is a consequence of salinity-induced water deficit, resulting in stunted growth and reduced leaf size described earlier.…”
Section: Resultsmentioning
confidence: 78%
“…Similarly, Sun et al (2015) documented that the SPAD readings of M. arboreus, R. brittoniana, and V. ·hybrida did not change, but S. farinacea and S. leucantha decreased significantly when irrigated weekly with saline solution at an EC of 10.0 dS · m -1 for 8 weeks. In a study of rose rootstocks by Niu et al (2008), Rosa ·fortuniana had greater SPAD readings compared with R. ·multiflora and R. ·odorata when irrigated with saline solution at an EC of 6.0 dS · m -1 for 15 weeks. These results consistently indicated that salinity stress negatively affected the chlorophyll content and the effect is dependent on plant species.…”
Section: Resultsmentioning
confidence: 99%
“…However, average value of conductivity (Table 3) in the FS during the present study is twice higher than that of Kengne et al (2008). Studying the effects of saline water irrigation on plants, Niu et al (2008) have observed the foliar discoloration and the decrease of visual score by 4 points of the three rose species that they studied. The effluent from a conventional activated sludge system treating saline tannery wastewater have caused growth inhibition of Trifolium pratense at concentrations higher than 25% while Arundo donax and Sarcocornia fruticosa have showed good performances (Calheiros et al, 2012).…”
Section: Fecal Sludge Application Effects On Plant Dynamicmentioning
confidence: 46%
“…Each STRB surface was divided into 9 equal squares in order to have a precise assessment of the total number of plants and their mean height. For each square, the wilting and discoloration (yellow or brown color of drought) indicator was evaluated according to the visual score in Table 2 (Niu et al, 2008).…”
Section: Monitoring Plant Morphologymentioning
confidence: 99%
See 1 more Smart Citation